SERVICE QUALITY INFRASTRUCTURE OF TRAVEL AGENCIES IN MALAYSIA - Azrin Abdul Razak; Ikmal Malik; Grace Derioh; Sitti Ulfa Rani (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2022)
Any service organisation's success hinges on the quality of its services. The Malaysian tourism industry's rapid growth has forced travel firms to recognise the necessity of service enhancement to achieve a competitive advantage. The study adopted experimental techniques in achieving its aim to completely comprehend the processes and systems that relate to travel agency service and quality management practices. From a list of travel agencies in Kuala Lumpur, Malaysia's capital city, 100 were chosen. Primary data was gathered through a survey questionnaire, while secondary data was gathered through websites and brochures from organisations. The result of the study shows that the monitoring infrastructure was ranked first among the four functions tested to determine the level of infrastructure support for delivering quality service in a travel agency, followed by the design function, the marketing function, and the customer service function. The study findings will be helpful to travel agencies and other tourism-related businesses to determine service quality and develop acceptable quality perception metrics in the context of services.Keywords: Service Quality, Travel Agency, Tourism Management